Rancang Bangun Mesin Automatic Seaweed Washing Kapasitas 25 Kilogram per Proses - Muhammad Habib Abdu Kafi; Ali Imron; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Seaweed is one of the common natural resources in Indonesia. But the seaweed processing in the society still ineffective because some of the washing process are still using manual process, and the expensive price of seaweed washing machine becoming the reason of the people using manual process. To increase and maximizing production output of the seaweed a seaweed washing machine is used to make the process easier andimproving value for processing or selling. Methods that the writer’s use to designing seaweed washing machine is ulrich method through choosing few design concepts, computer aided design (CAD) for design drawing making, fabrication, machine components assembly and trials to determine production output from seaweed washing machine which is 25 kgs per process. Based on planning and design result there are seaweed washingmachine with main dimensions 1470 mm x 537 mm x 950 mm. Next for the trial resulting in 25 kgs output of gracilaria seaweed and water in 1 washing for 5 minutes. Seaweed wholeness condition assumed 90% with good condition and solids that dissolved in water after the first and second washing process are less than 1000 mg/L which is 465 mg/L.